Cursed Capital: the Economic Impact of the Transatlantic Slave Trade on Walcheren around 1770 - de Kok, Gerhard (TSEG - The Low Countries Journal of Social and Economic History, 2016)
The island of Walcheren in the province of Zeeland was the largest Dutch slaving center in the eighteenth century. While the profitability of the slave trade itself was limited, it had important local economic effects. A clue comes from the excellently preserved archive of the largest slave trader: the Middelburgse Commercie Compagnie (MCC). Combining the figures in the MCC archive with some experimental calculations, it is estimated that around 1770 about a tenth of the income earned by inhabitants of Middelburg was connected to the trade in enslaved Africans. For the more specialized and smaller city of Flushing, this figure was likely closer to a third of all income.